2022
DOI: 10.1177/23969873221145771
|View full text |Cite
|
Sign up to set email alerts
|

Association between type of intervention center and outcomes after endovascular treatment for acute ischemic stroke: Results from the MR CLEAN Registry

Abstract: Background: Endovascular treatment (EVT) for acute ischemic stroke (AIS) is performed in intervention centers that provide the full range of neuro(endo)vascular care (level 1) and centers that only perform EVT for AIS (level 2). We compared outcomes between these center types and assessed whether differences in outcomes could be explained by center volume (CV). Patients and methods: We analyzed patients included in the MR CLEAN Registry (2014–2018), a registry of all EVT-treated patients in the Netherlands. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The DAWN and DEFUSE-3 trials demonstrated the efficacy of mechanical thrombectomy in the extended time window up to 24 hours from time last seen well. The MR CLEAN LATE, 8 CLEAR, 34 and RESCUE BT studies 33 showed that selection of patients to EVT in the late window can be performed by evaluation of a good NCCT and/or good collaterals on CTA, particularly in light of the positive results from the large ischemic core trials. The performance of such imaging paradigms is more widely available and accessible compared with advanced imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DAWN and DEFUSE-3 trials demonstrated the efficacy of mechanical thrombectomy in the extended time window up to 24 hours from time last seen well. The MR CLEAN LATE, 8 CLEAR, 34 and RESCUE BT studies 33 showed that selection of patients to EVT in the late window can be performed by evaluation of a good NCCT and/or good collaterals on CTA, particularly in light of the positive results from the large ischemic core trials. The performance of such imaging paradigms is more widely available and accessible compared with advanced imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The MR CLEAN LATE trial demonstrated better outcomes in patients treated with EVT in mRS ordinal shift analysis. 8 Other trials including RESILIENT Extend (NCT02216643) and NO-CTP (NCT05230914) will also evaluate the use of NCCT for patient selection to EVT in the late window.…”
Section: Neuroimaging Selection In the Late Time Windowmentioning
confidence: 99%
See 1 more Smart Citation
“…As the community is still adapting to this new evidence, the MR CLEAN LATE trial (Endovascular Treatment of Acute Stroke for Late Arrivals Trial) 4 and recent trials on large ischemic volumes 5 suggest that advanced imaging may lose its central role even for late window or large core patients, emphasizing that with sound clinical judg ment, EVT is rarely harmful in proximal occlusions.…”
Section: Guiding Revascularization Therapies: Changing Lanesmentioning
confidence: 99%
“…However, these recommendations may change based on the results of recently completed and ongoing large core studies. [8][9][10] The routine use of multimodal imaging offers additional advantages in stroke research based on a survey of the workshop participants. For example, at comprehensive stroke centers, the routine use of multimodal imaging is recommended to facilitate endovascular stroke research aimed at refining EVT eligibility criteria (eg, There is no consensus of the optimal imaging protocol for primary and comprehensive stroke centers.…”
Section: Special Reportmentioning
confidence: 99%